A case study : flood mitigation project in Kelantan - Nur Shahidah, Ahmad Sobri (2012)
In 2004, Kelantan is one of the states that most affected by the flood event. The disaster has caused a lot of damages and losses to resident. Although flood is difficult to avoid, the impact still can be minimize by some actions and precaution. The objectives of this study are to identify the worst area affected by flood in Kelantan and identify the flood mitigation projects that have been implemented in Kelantan. Data needed in this study are rainfall data, water level data and the details on the implemented project. At the same time, site visits and investigation were also conducted to understand the existing condition as well as the problems faced in the studied area. Besides that, set of questionnaires also were distributed among residents in some district in Kelantan. From the analysis, the area that has been identified worst affected by flood are Tumpat, Pasir Mas and Kuala Krai. Some of the flood project mitigation was applied at Bukit Sireh and Taman Warisan in Kuala Krai and the same goes to Jalan Sirat. In the end of this study, recommendations in order to overcome this flood problem in study area such as constructing a strong levee at low lying area as well as deepening and widening of the river and the drainage have been proposed..